Nutritional Practices and Growth in Premature Infants After Surgical Necrotizing Enterocolitis. Issue 1 (July 2017) - Lin, Grace C.; Robinson, Daniel T.; Olsen, Steven; Reber, Kristina M.; Moallem, Mohannad; DiGeronimo, Robert; Mulroy, Cecilia; Datta, Ankur; Murthy, Karna
ABSTRACT: Objective: The aim of the study was to describe the nutritional provisions received by infants with surgical necrotizing enterocolitis (NEC) and the associated effects on short-term growth. Methods: Through the Children's Hospitals Neonatal Database, we identified infants born ⩽32 weeks' gestation with surgical NEC from 5 regional neonatal intensive care units for 4 years. Excluded infants had isolated intestinal perforation and died <14 days postoperatively. Infants were stratified by their median parenteral protein dose (low [LP] or high [HP] protein) for the first postoperative week. The primary outcome was postoperative weight growth velocity. Growth (weight, length, and head circumference [HC]) was measured and the effects related to protein dose were estimated using multivariable analyses. Results: There were 103 infants included; the median parenteral protein dose received was 3.27 g · kg −1 · day −1 (LP: 2.80 g · kg −1 · day −1 ; HP: 3.87 g · kg −1 · day −1 ). Postoperative weight (11.5 ± 6.5 g · kg −1 · day −1 ) and linear growth (0.9 ± 0.2 cm/wk) were similar regardless of dose ( P > 0.3 between groups for weight and length). Unadjusted and independent associations were identified with HC changes and HP dose (β = 0.1 cm/wk, P = 0.03) after adjusting for gestational age, the presence of severe bronchopulmonary dysplasia, short bowel syndrome, blood stream infection, severe intraventricular hemorrhage, small for gestational age, and calorie intake. Eventual nonsurvivors received 18% less protein and 14% fewer calories over the first postoperative month. Conclusions: Postoperative protein doses in infants with surgical NEC appear related to increases in HC. The influence of postoperative nutritional support on risk of adverse outcomes deserves further attention. Abstract : Supplemental Digital Content is available in the text